Impacts of Global Change on the Spatial Dynamics of Treeline in Venezuelan Andes - Chacón-Moreno, Eulogio; Rodríguez-Morales, Mayanín; Paredes, Daniela; Suárez del Moral, Patricia; Albarrán, Anderson (Frontiers in Ecology and Evolution, 2021)
The treeline in the Andes is considered an essential ecotone between the Montane forest and Páramo. This treeline in the Venezuelan Andes corresponds with a transitional ecosystem defined as the Páramo forest. In this work, we identify and analyze the impact of climate warming and land transformation as agents altering the Páramo forest ecosystem's spatial dynamics along the Venezuelan Andes' altitudinal gradient. We carry out multitemporal studies of 57 years of the land transformation at different landscapes of the Cordillera de Mérida and made a detailed analysis to understand the replacement of the potential ecosystems' distribution. We found that the main ecosystem transition is from Páramo to the Páramo forest and from Páramo to the Montane forest. Based on the difference between the current lower Páramo limit and the Forest upper limit for 1952, the treeline border's displacement is 72.7 m in the 57 years of study, representing ~12.8 m per decade. These changes are mainly driven by climate warming and are carried out through an ecological process of densification of the woody composition instead of the shrubland structure. We found that Páramo forest ecosystems practically have been replaced by the Pastures and fallow vegetation, and the Crops. We present a synthesis of the transition and displacement of the different ecosystems and vegetation types in the treeline zone. The impact of climate warming and deforestation on the Páramo forest as a representative ecosystem of the treeline shows us that this study is necessary for an integrated global change adaptation plan.